Prevalence of medication administration errors and its determinants among nurses in Ethiopia: a systematic review and meta-analysis - Muluken Amare Wudu; Ewunetie Mekashaw Bayked; Yemane Eshetu Bekalu; Tarikua Afework Birhanu (BMC Nursing)
Abstract Background Despite nurses being the backbone of patient care, medication administration errors (MAEs) remain a serious risk to patient safety in low-income countries, including Ethiopia. However, the previous review was outdated, included fewer than 10 studies, focused solely on tertiary hospitals, and did not pool determinants. As a result, this meta-analysis aimed to determine the pooled prevalence of MAEs and their determinants among nurses in Ethiopia, addressing gaps in the study setting, time, and outcomes. Methods The study protocol was registered in PROSPERO. Observational studies conducted in Ethiopia and published in English from 2010 to 2024 were included. PubMed, Scopus, EMBASE, and Google Scholar databases were used to search for studies. The Joanna Briggs Institute (JBI) checklist was used to evaluate the quality of the studies, with three authors participating in the process. Data analysis for the pooled magnitude of MAEs and their determinants was conducted using STATA 17 software with the DerSimonian and Laird random-effects model. Heterogeneity was assessed via Cochrane’s Q-test and the I² statistic, while publication bias was evaluated through funnel plots, Egger’s test, and Doi plot. Results Of the 264 articles retrieved, 18 studies, including 4,314 nurses, were included in the meta-analysis. The pooled magnitude of MAEs among nurses in Ethiopia was 57% (95% CI: 49–64%). Moreover, inadequate work experience [OR = 3.64; 95% CI: (3.32, 3.96); I²=0.00%], interruptions [OR = 3.53; 95% CI: (3.19, 3.87); I²=0.00%], lack of guideline availability [OR = 2.14; 95% CI: (1.63, 2.66); I²=0.00%], lack of training [OR = 3.22; 95% CI: (2.67, 3.77); I²=0.00%], night shifts [OR = 3.89; 95% CI: (3.37, 4.41); I²=0.00%], and a nurse-patient ratio ≥ 1:10 [OR = 2.82; 95% CI: (2.19, 3.45); I²=0.00%] were identified as determinants of MAEs among nurses. Conclusion The magnitude of MAEs in the current review was substantially higher compared to global reports and studies in Africa, highlighting the need for urgent intervention. Furthermore, inadequate work experience, interruptions, lack of guideline availability and training, night shifts, and a nurse-patient ratio ≥ 1:10 were identified as determinants of MAEs among nurses. This suggests that providing training, disseminating guidelines in accessible formats, improving staffing ratios, and fostering a culture of safety are crucial steps to reduce MAEs. Clinical trial number Not applicable.